Multicentric Histocytosis Mimicking Histoid Leprosy- A Case Report - Purohit, Dr. Saroj; Sharma, Dr. Priyanka; Meena, Dr. Ram Singh; Bargujar, Dr. Babita (International Journal of Innovative Research in Medical Science, 2016)
Multicentric reticulohistiocytosis (MRH) is a very rare systemic disease with variable phenotypic presentation having predominant joint and cutaneous manifestations most commonly affecting women in middle age. The diagnosis is often overlooked because of the rarity of this condition. Here in, we are reporting a case of Multicentric reticulohistiocytosis presenting as multiple erythematous nodules all over the body mimickin as Histoid leprosy along with systemic involvement.